PENGARUH PENINGKATAN SUHU DAN BESARAN ARUS TERHADAP TAHANAN PENGHANTAR KABEL LISTRIK TEGANGAN RENDAH JENIS NYM - Kiki Rosiana Dewi; Suyitno; Nur Hanifah Yuninda (Journal of Electrical Vocational Education and Technology, 2019)
The purpose of this research is to know about influence of temperature increasing and current rate on the conductor resistance, the conductor temperature and the conductor power losses of the conductors of the cable brand A and brand B due to the effect of increasing temperature and current magnitude. Increasing the temperature and currents rate have a bigger influence on the increase of temperature conductor, the resistance conductor and conductor losses the electric cable brand B compared to the brand A. The electricity cable brand B is a conductor that does not have standardization suitable for electrical installation. The conductor of brand A electrical cable is a cable conductor that has standardization and is suitable for use. At chamber temperature of 25 ℃ the test current 5 A the value of conductor resistance 2 x 1.5 mm2 of brand A increases by 11,90 mΩ while brand B increases by 23.32 mΩ. The maximum conductor resistance according to standardization is 12,10 mΩ for a cross section area of ​​1.5 mm2. Based on the test results, each increase in temperature and the currents rate have an influence for increasing value of the conductor temperature, the conductor resistance and conductor losses are bigger. The relationship between the conductor resistance and the cross-sectional area is that the smaller the cross-sectional area, the bigger the conductor resistance. ABSTRAK Tujuan dari penelitian ini adalah untuk mengetahui pengaruh peningkatan suhu dan besaran arus terhadap nilai tahanan penghantar, suhu penghantar dan rugi daya penghantar pada penghantar kabel listrik merk A dan merk B. Peningkatan suhu dan besaran arus mempunyai pengaruh yang lebih besar terhadap kenaikan suhu penghantar, tahanan penghantar dan rugi daya penghantar kabel listrik merk B dibandingkan dengan merk A. Penghantar kabel merk B merupakan penghantar yang tidak memiliki standarisasi layak pakai dalam instalasi listrik. Penghantar kabel listrik merk A merupakan penghantar kabel yang telah memiliki standarisasi dan layak pakai. Pada suhu chamber 25 arus pengujian 5 A nilai tahanan penghantar 2 x 1,5 mm2 merk A meningkat sebesar 11,90 mΩ sedangkan merk B meningkat sebesar 23,32 mΩ. Nilai tahanan penghantar maksimal sesuai dengan standarisasi adalah sebesar 12,10 mΩ untuk luas penampang 1,5 mm2. Berdasarkan hasil pengujian, setiap peningkatan suhu dan besaran arus nilai memiliki pengaruh terhadap kenaikan nilai suhu penghantar, tahanan penghantar dan rugi daya penghantar semakin besar. Hubungan antara tahanan penghantar dengan luas penampang yaitu dengan semakin kecil luas penampang maka nilai tahanan penghantar semakin besar.